Maternal and Child Awareness and Expectations of Child Overweight - Brødsgaard, Anne (Obes Facts, 2011)
OBJECTIVE: We investigated mothers’ and children’s assessments of body weight and their expectations about perceived body size in relation to overweight of the children. METHODS: We performed a case-control study of 111 cases of overweight children and 149 controls of non-overweight children (mean age 8.1 years) and their mothers. All were examined and interviewed about their assessment of body weight and their perception of a normal, attractive and acceptable body size. RESULTS: Case children were less able than control children to correctly assess their own body weight (p < 0.001), as were mothers of overweight children (MOC) to assess their children’s body weight (p < 0.001). The majority of mothers from both groups wished their children to have a normal body size, but 18% of MOC wished their children to have an overweight body size (p < 0.013). The majority of case children, control children and mothers found a normal body size for boys and girls to be the most attractive and socially acceptable, but more MOC found overweight among boys to be the most attractive (p = 0.006). CONCLUSION: Overweight children and their mothers show increased uncertainty in the assessment of overweight and obesity, but the perception of a normal, attractive and socially acceptable body size is not distorted.